PENGARUH PEMBELAJARAN KEWIRAUSAHAAN DAN PEMANFAATAN MEDIA SOSIAL TERHADAP MINAT BERWIRAUSAHA DI MAHASISWA FKIP UNS - Mesiana Listiawati; Cicilia Dyah; Susantiningrum Susantiningrum (Jurnal Kewirausahaan dan Bisnis, 2020)
Entrepreneurial learning is one of the compulsory subjects that must be attended by students, but interest in student entrepreneurship is still low. The purpose of this study is to determine : (1) the effect of entrepreneurial learning on entrepreneurship interest of the student of Teacher Training and Education Faculty; (2) the effect of using social media on entrepreneurship interest of the student of Teacher Training and Education Faculty; and (3) the effect of entrepreneurial learning and using of  social media together on entrepreneurship interest of student of Teacher Training and Education Faculty of Sebelas Maret University. The research method used is descriptive correlational with a quantitative approach. The population in this study were all students who have taken entrepreneurship courses which consists 1863 students. The research sample are 96 students, which taken with a proporsional random sampling. Data collection technique carried out by using questionnaire. Data analysis techniques use multiple linear regression analysis using SPSS release 24.0. The result show that: (1) there is a significant positive effect of learning entrepreneurship on entrepreneurial interest (t-count (3.087) > t-table (1.9855)). (2) there is a significant positive effect of utilization social media on entrepreneurial interest (t-count (5.033) > t-table (1.9855))and (3) there is significant positive effect of learning entrepreneurship and utilization social media together on entrepreneurial interest (F-count (26.294) >F-table (3.09)). The conclusion in this study is that there is a significant influence on entrepreneurial learning and using of social media on entrepreneurship interest.Key words: entrepreneurial learning, entrepreneurship, social media